Methanolysis of duckweed and azolla: A comparative analysis - Rohim, R.; Isa, K. M.; Abdullah, T. A. T.; Rashid, R. A.; Mohd Aizudin, Abd Aziz (IOP Science, 2021)
This paper compares the bio-oil and chemical compositions produced from methanolysis of duckweed and Azolla. The methanolysis was carried out at 230°C, 250°C and 300°C for 30 minutes using the CJF-0.1L reactor. Oil yield produced from azolla was 34% and this is 3% higher as compared to the bio-oil yield produced by duckweed at 250°C. The Gas Chromatography Mass Spectrometry (GCMS) analysis showed that alcohol, ketone, amine, ether and ester compositions in the bio-oil produced from duckweed were slightly higher than azolla. However, carboxylic acids, amide and phenol compounds in the bio-oil produced from azolla are different and higher than duckweed. The results suggest that duckweed and azolla are the potential feedstocks from aquatic biomass to be further investigated for bio oil use.